Production and characterization of activated carbons made from sunflower stems - Valente Nabais, Joao (2012)
Activated carbons (ACs) are artificial materials, prepared from natural or synthetic precursors that are worldwide extensively used. The ACs main characteristics are the noticeable adsorption capabilities provided by the highly developed porous structure and the rich surface chemistry. Because of their versatility and properties the final material can be tailored to have specific properties suitable for a wide range of applications such as medical uses, gas storage, removal of pollutants and odours, gas separation and purification as well as in catalysis. With the increase of activated carbon demand, one of the main challenges lies in the attempt to find new precursors, which are cheap and accessible with good valorisation potential, like industrial and agricultural residues. In the present work we report the production of ACs from sunflower stems, an agricultural by-product, through a physical activation process by CO2 and H2O, using a single step carbonisation at 400ºC, which as far as it came to our knowledge was never made for this precursor.